Catastrophic health expenditure and the risk of depression among middle-aged and old people in China: a national population-based longitudinal study - Yaping Wang; Min Liu; Jue Liu (Epidemiology and Psychiatric Sciences, 2023)
Abstract Aims To estimate the association of catastrophic health expenditure (CHE) with the risk of depression in middle-aged and old people in China.